(untitled) (Research, Society and Development, 2024)
Canine caudal vertebrae make up the dog’s tail, varying in number and size among breeds, and are fundamental for balance, communication, and emotional expression. Tail docking is a surgical procedure that amputates these vertebrae. However, when performed for aesthetic or cultural reasons, this practice has generated intense debates and significant controversies, raising questions about the justification for its continuation. Based on this, this work aims to describe the anatomy of canine vertebrae and tail docking, highlighting the potential harm that such mutilation can cause to these animals, supported by a literature review. Research indicates that the tail is essential not only for canine communication, allowing dogs to express a range of emotions and intentions, but also plays a crucial role in balance, especially during running and performing agile movements. Therefore, tail removal can significantly interfere with dogs’ behavior and ability to express body language, in addition to potentially causing pain, discomfort during the postoperative period, and leading to serious complications such as infections and the development of amputation neuroma, a painful condition that occurs at the amputation stump. Currently, many countries have adopted laws and regulations that restrict or prohibit tail docking in dogs, except when necessary for medical reasons. The growing awareness of animal welfare has led to a change in attitude towards this practice, with more owners opting to keep their dogs’ tails natural.